Pengaruh Aroma Terapi Lavender Terhadap Kualitas Tidur Pada Lansia - Nur Shadrina, Nadhilah; Nadhilah Nur Shadrina; Aulia Rahayu Nur Fadila; Evi Nurhayati; Muhammad Firmansyah; Ummi Malika Balqis (STIKES Permata Nusantara Cianjur, 2024)
Summary One of the main characteristics of human aging is a decline. in terms of mental, social, psychological, physical, and physiological processes Roughly 40 to 50 percent of elderly people suffer from sleep disorders, and most of them are predisposed to them because of a number of factors, including the fact that their sleep patterns change regularly. Method: A literature review of a few chosen papers was employed in this study. The participants discussed two main points regarding the effects of lavender aromatherapy: firstly, lavender scent improves sleep quality and reduces insomnia in the elderly